Developing Engaged Scholars: The Graduate Advisor-Advisee Relationship - Lorilee R. Sandmann; Audrey J. Jaeger; Jihyun Kim (Adult Education Research Conference, 2010)
A critical dimension in the development of emerging engaged scholars is the advisor-advisee relationship. A multiyear, multiuniversity study of doctoral students interested in community-engaged scholarship and their advisors found that advisors influenced their advisees’ specific approach to community engagement; advisees built extensively on their own community-based experiences and even pushed their advisors in co-learning about communityengaged scholarship; and advisors and advisees shared recognition of lack of support for community engagement but pursued it anyway.